PENGARUH TERAPI AKTIVITAS KELOMPOK SOSIALISASI TERHADAP TINGKAT DEPRESI DI RUMAH SAKIT JIWA DAERAH SURAKARTA - Susilowati, Kiki; Widodo, Arif (Jurnal Berita Ilmu Keperawatan, 2009)
Data from Director General of Constructs Medical Service Health Department of Indonesia conclude that soul trouble type which at most is depression (10%). There are many of technique to reduce it is called therapy of group activity. Purpose to know group activity therapy socialization influence to level of depression in psychiatry Hospital of Surakarta (RSJD). Method Queasy experimental, pretest-posttest with control group design. Population at this research is all depression patient takes care of lodging patients divided into 2 group. Data analysis applies techniques of Independent t test. Conclusion The result of research shows (1) level of responder depression group of treatment before treatment giving of activity therapy socialization of group (pre test) mostly is weight depression (56%), while after treatment (post test) light and medium mean (31%), (2) level of responder depression group of control at pre test and post test most of is weight (69% to 63%), and (3) there is treatment giving influence of activity therapy group of socialization to level of depression in Psychiatry Hospital of Surakarta (RSJD), t-test in 3,065 with 0,005 probability.